Accessible design features and home modifications to improve physical housing accessibility: A mixed-methods survey of occupational therapists. Issue 3 (July 2022) - Wellecke, Cornelia; D'Cruz, Kate; Winkler, Di; Douglas, Jacinta; Goodwin, Isabella; Davis, Elise; Mulherin, Peter
Abstract: Background: Despite the number of older people and people with disabilities increasing in Australia, it is unclear which housing design features are needed to support physical housing accessibility for people with and without disabilities across the lifespan. Objective: This study drew upon the experience of occupational therapists to investigate accessible housing design features and home modifications to support aging in place and discharge from hospital to home. Methods: A cross-sectional online survey exploring housing design features and home modifications was completed by 144 Australian occupational therapists over six weeks in 2021. Descriptive quantitative and qualitative data analyses were used. Results: For both aging in place and hospital discharge, the most important housing design features included step-free access to the dwelling, large step-free showers, and bathroom and bedroom space on the ground floor. Qualitative findings also highlighted the importance of preparing for home modifications, such as reinforcing bathroom walls to support the post-build installation of grab rails. The most frequently needed modifications were for bathroom features, while structural changes to the dwelling were the most time-intensive modifications, requiring more than six weeks to be completed. Conclusions: External access to the home and internal access to bedroom and bathroom facilities can support aging in place and hospital discharge and mitigate the need for costly and time-intensive home modifications. While this study was conducted in Australia, the findings have relevance outside of this context, and are important for ensuring equitable accessibility for people with and without disabilities across the lifespan. Highlights: Home modifications are frequently needed but are time-consuming to be implemented. Accessible housing design mitigates the need for costly home modifications. Step-free external access and internal bathroom access are key to accessible housing design. Mandatory minimum accessible design can improve housing accessibility for all people. Findings of this study may encourage adoption of minimum accessibility standards.